2005
DOI: 10.1002/art.20965
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin‐22 in rheumatoid arthritis: Potential role as a proinflammatory cytokine

Abstract: Conclusion. These data suggest that IL-22, produced by synovial fibroblasts and macrophages, promotes inflammatory responses in RA synovial tissues by inducing the proliferation and chemokine production of synovial fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
282
2
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(302 citation statements)
references
References 20 publications
13
282
2
3
Order By: Relevance
“…This result stands in contrast to the argument that IL-22 has a proinflammatory function (45)(46)(47). The evidence for the latter comes primarily from studies describing IL-22-mediated induction of defensin genes (45,47).…”
Section: Anti-inflammatory Signals Generated By the Il-27 And Il-22 Rmentioning
confidence: 64%
“…This result stands in contrast to the argument that IL-22 has a proinflammatory function (45)(46)(47). The evidence for the latter comes primarily from studies describing IL-22-mediated induction of defensin genes (45,47).…”
Section: Anti-inflammatory Signals Generated By the Il-27 And Il-22 Rmentioning
confidence: 64%
“…Of note, other than STAT3, IL-22 is also known to activate other signaling pathways such as the three major MAPK pathways, ERK1/2, JNK and p38 kinase pathways. 22,35,36 These pathways, which have been implicated in transformation and tumor progression in many human cancers, 37,39 were confirmed to be activated by IL-22 in ALK þ ALCL cell lines. NPM-ALK is also a known activator of the ERK1/2 signaling pathway and has been shown to enhance cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 94%
“…This, however, does not exclude the constitutive production of other soluble factors that might be involved in the constitutive expression of chemokines or other mediators of inflammation that were not analyzed in the current study. Indeed, earlier studies have demonstrated the constitutive production of IL-6, IL-11 (10), or IL-22 (48) by RASFs.…”
Section: Discussionmentioning
confidence: 98%